Perencanaan Peningkatan Kualitas Produk Kasur Karpet dengan Metode Kano dan House of Quality - Taptajani, Dedi Sa’dudin; Chandrahadinata, Dody; Irsyadilhaq, Imam Nursalam (Institut Teknologi Garut, 2023)
Ikmal Surpet is a company that produces Carpet Mattresses. The vision of the company is to make a company in the field of superior and quality mattresses while its mission itself is to maintain and improve the quality of superior local products. In line with the Company's Vision and Mission, the aim of this research is to find out what attributes need to be considered, maintained and improved regarding the level of satisfaction and quality of surpet products (carpet mattresses). Planning to improve the quality of surpet products (carpet mattresses). The Kano method is used to find out what attributes need to be paid attention to, maintained and improved. The House of Quality method is used to make improvement proposals. The research results show that there are two attributes that need to be considered, namely: the product has neat stitching and the product design has its own characteristics, there are five attributes that need to be maintained, namely: the product uses quality raw materials, the upholstery feels soft & soft, the product can long lasting, varied product designs, and attractive product designs., and what attributes need to be improved, there are two attributes, namely: flexible surpet products, and having sizes according to needs. To plan to improve the quality of carpet mattress products, nine attributes were obtained which would become priority improvements with their respective technical responses.